Path Planning for Multi-Object Push Problems in Continuous Domain. Issue 30 (2019) - Swift, Marcus; Jayakody, Hiranya; Whitty, Mark
Abstract: The task of bulldozing has many aspects that need more research before they can be fully automated. This paper presents a new method for calculating a path for vehicles tasked with pushing multiple objects to multiple goal locations. Unlike previous approaches which either focus on a single object, apply both push and pull operations, or operate in discrete domain, this solution works in a continuous space whilst handling multiple objects in a push-only scenario and doesn't use computationally heavy methods to find a potential path planning solution. To achieve the results, two graph structures, one for the active vehicle and one for the passive pushable objects, is used. These graphs are then combined with an A ⁎ Search Algorithm to find a correct path for the bulldozer to take. The algorithm is tested on a Microban problem set which results in a 96% success rate.